THE IMPORTANCE OF USING VISUAL AIDS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article highlights the role and significance of using visual aids in the modern educational process. Visual materials—such as images, tables, diagrams, models, or multimedia—significantly enhance students’ understanding of the subject, improve memory retention, and increase active participation in lessons. The article emphasizes how visual aids make the learning process more engaging, simplify complex concepts, and effectively develop students’ thinking and interest, supported by scientific evidence and practical examples. Additionally, recommendations are provided for teachers on how to select appropriate visual aids, adapt them to the lesson content, and use them to achieve pedagogical goals. Research results show that the effective use of visual aids is one of the key factors in improving the quality of education.